Análise do processo de conclusão dos cursos de graduação de uma IES pública - Rosante, Evandro Marcos (Universidade Federal de São Carlos, 2020)
The Academic Registration Section (SeRA) has as main attribution the execution of the process of undergraduate courses conclusion of the Federal University of São Carlos (UFSCar). This process covers the activities of degree graduation and issuing diplomas. Adversities, such as lack of formal and documented procedures, result in setbacks that hinder the work of the servers and can lead to errors and delays. The objective of this work is to analyze and propose improvements for the process of undergraduate courses conclusion of the UFSCar. The present work was developed through the administrative approach of Process Management. The case study methodology was adopted, developed in six steps, with the techniques of document analysis, participant observation, process mapping and brainstorming. In step 1, the context of the study was presented, as well as the general and specific objectives, as well as their justifications. In step 2, the theoretical review on the administrative approach to Process Management and on federal legislation was elaborated. In the third stage, the Pilot Test was developed with the description of the organizational structure and the rules of the studied institution, as well as the mapping of the current situation (AS IS) of the degree graduation process, through the Business Process Model and Notation (BPMN). In the fourth stage, the mapping of all phases of the process was developed, as was developed the SIPOC model, to identify the inputs and outputs of the processes, and the Responsibility Matrix that helped in the identification of those responsible for each process activity. In step 5, 13 critical factors were identified from the analysis of the mapped processes. In the last stage, 13 improvement proposals were elaborated, with their justifications and presentation of the implementation feasibility. The last stage also showed the redesign of all stages of the process, generating the flows of the future process mapping (TO BE) and the proposal for the future design of the flow of the process of issuing digital diplomas. It was concluded that the process of undergraduate courses conclusion can be improved with the proposals suggested in this study, however, with the exception of the importance of the consent of the management of the University for a possible analysis and discussion of the implementation of the suggestions.
Analysis of process of undergraduate courses conclusion of a public institution of higher education
Keywords: Colação de grau; Emissão de diplomas; Universidade pública; Gestão por processos; BPMN; Academic management; Degree graduation; Public university; Process management; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS